Biological and Chemical Monitoring of Rostov NPP as Effective Tool to Prevent Biological Disturbances in the Circulation and Technical Water Supply Systems - O. I. Gorskaya (Глобальная ядерная безопасность, 2022)
The technical and circulating water supply systems of nuclear power plants use water from natural or technical water bodies to provide the water supply to the nuclear power plants. Individual elements and equipment of technical water, are called technical water supply systems. In technical and circulating water supply systems, biological fouling is a collection of microorganisms, algae, molluscs, sponges, bryozoans and other biological organisms that have settled and developed on the heat exchange surfaces of units, in pipelines and on the structures of circulating water coolers. This fouling is caused by the introduction of micro-organisms and dispersal forms of fouling organisms with water from the source. In order to prevent and eliminate biological fouling on the equipment of technical and circulating water supply systems of nuclear plants, Rosenergoatom Concern JSC has adopted a production programme aimed at regular biological and chemical monitoring of water supply systems of nuclear plants.